Caracterización del Suelo a través de la Resistividad Eléctrica de un Terreno entre el Bloque 2 y 7 de la Sede Circunvalar en la Universidad Antonio Nariño (2024)
The electrical resistivity of the soil is a key property in the characterisation of the same, this consists of the capacity that the soil has to conduct electricity through itself; this property has diverse applications in the field of civil engineering. The purpose of this work is to characterise a soil located between blocks 2 and 7 at the circumvalar headquarters of the Antonio Nariño University using the electrical tomography method and the objective comparison between the existing literature and the soil studies available to the university, which date back to 2012.